Rekomendasi Upaya Pemasaran dengan Model Value-Based Matrix pada Marketing 3.0 untuk Meningkatkan Hunian Unit Obsgyn RS ‘Aisyiyah Bojonegoro - Fahtia Nur Rosyida (Qanun Medika - Jurnal Kedokteran FK UMSurabaya, 2018)
ABSTRACTThe occupancy rate of obsgyn ward ‘Aisyiyah Bojonegoro Hospital is still very low (33,5%) compared to occupancy target (50.0%) in last five years. The purpose of this study was to identify the expectations of consumers to 4Ps (Product, Price, Place, Promotion) obsgyn inpatient services in mind, heart, spirit and the mission, vision, and values ‘Aisyiyah Bojonegoro hospital. Further arranged on marketing efforts with Value-Based Matrix models on marketing 3.0 for an alternative answer to the problems of dwelling of obsgyn ward ‘Aisyiyah Bojonegoro Hospital. This is a descriptive with cross-sectional approach study. The data was taken in January-August 2016. The data used are primary and secondary data. Primary data was taken with a questionnaire guidance to 152 patients respondent from obsgyn clinic specialist and 22 patients respondent from Maternal and Child Health (MCH) outpatient 'Aisyiyah Bojonegoro Hospital. The sampling method was accidental sampling. Secondary data such as mission, vision, and values are taken from the profile hospital hospital. Analysis of the respondents expectations and the hospitals mission, vision, and values are taken to be FGD material with hospital management to explore alternative marketing efforts that will be done. The researchers analysis from FGD results lead to the conclusion in the form of 19 marketing efforts recommendations based on value-based matrix in marketing 3.0 by identifying consumer expectations and the mission, vision, values hospital. These marketing efforts recommendations is expected to increase the occupancy rate of obsgyn ward ‘Aisyiyah Bojonegoro Hospital.Keywords:Marketing Efforts, Value Based Matrix, Marketing 3.0.